Formulasi dan evaluasi sediaan masker gel peel-off ekstrak aseton bekatul padi (Oryza sativa) kombinasi dengan minyak atsiri kulit jeruk Bali (Citrus maxima) - Hadi, Ismanurrahman; Aulia, Diva; Irawan, Ade (Universitas Muhammadiyah Magelang, 2023)
Rice bran (Oryza sativa) is a layer of bran that is separated from the rice during removal during milling. In some literature, it is stated that rice bran has ingredients such as B complex vitamins, B15, vitamin E, protein, minerals, fat, fiber, calcium, essential amino acids and phenolic acids. This study aims to determine the formulation for gel peel-off masks with the active ingredient of rice bran acetone extract combined with grapefruit peel essential oil with concentrations of 5, 10, 15% (F1 without extract and F2, F3 and F4, each extract concentrations of 5%, 10%, and 15 %). Physical evaluation of peel-off gel mask preparations was carried out by organoleptic test, pH test, homogeneity test, drying time test, spreadability test, adhesion test; followed by a hedonic (favorite) test. The results of the evaluation of physical properties show that the formulas F1, F2, F3 and F4 have good physical properties and appearance. The hedonic test conducted showed that the panelists liked the peel-off gel mask preparation with the F2 formula the most. Based on this, it can be concluded that, the best formula is F2 ( 5% extract).